Case study -- the shrimp export industry in Bangladesh: food safety in food security and food trade - Cato, James C.; Subasinge, S. (International Food Policy Research Institute, 2003)
By the end of the 1970s, the Bangladesh seafood processing industry had expanded rapidly. But sanitary facilities, technology adaptation, and adequate training did not keep pace. Shrimp exports suffered in the late 1970s, and the U. S. Food and Drug Administration placed seafood imports from Bangladesh under automatic detention. This was only the beginning of the export market problems arising from substandard product safety and quality that Bangladesh’s shrimp industry faced over the next two decades. This case study illustrates the actions taken by Bangladesh, with the aid of external partners, to overcome substantial obstacles to participation in world shrimp markets.